2015
DOI: 10.1007/s11912-014-0429-6
|View full text |Cite
|
Sign up to set email alerts
|

Respecting the Spiritual Side of Advanced Cancer Care: a Systematic Review

Abstract: Spirituality is among the resources that many turn to as they deal with a diagnosis of advanced cancer. Researchers have made much progress in exploring and understanding spirituality's complex and multifaceted role in the midst of metastatic disease. As a result, spirituality is seen as an important aspect of a holistic and respectful approach to clinical care for patients and their loved ones. In this article, we provide a systematic review of the literature related to the interface between spirituality and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 47 publications
0
34
0
3
Order By: Relevance
“…However, research investigating the impact of spiritual interventions on patients with cancer has also primarily studied Christian white populations. 51 Mindfulness-based stress reduction interventions have been shown to diminish psychological distress, sleep disturbances, and fatigue, while also improving QOL and spirituality in those with cancer. 52 Because spirituality contributes to QOL in black patients with cancer who experience pain, interventions aimed at enhancing spirituality care may be useful in improving overall QOL in this population.…”
Section: Discussionmentioning
confidence: 99%
“…However, research investigating the impact of spiritual interventions on patients with cancer has also primarily studied Christian white populations. 51 Mindfulness-based stress reduction interventions have been shown to diminish psychological distress, sleep disturbances, and fatigue, while also improving QOL and spirituality in those with cancer. 52 Because spirituality contributes to QOL in black patients with cancer who experience pain, interventions aimed at enhancing spirituality care may be useful in improving overall QOL in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Although a review found inconclusive evidence that interventions with spiritual or religious components for adults in the terminal phase of a disease may or may not enhance well-being (Candy et al, 2012), the importance of attending to patients' religious and spiritual needs is underscored by many Authors (Jim et al, 2015;Otis-Green et al, 2012). The primary objective of this intervention should be aimed at helping patients to find a meaning and a purpose of their past and present life experiences and achieving a sense of inner peace regardless of religious beliefs (Breitbart et al, 2012;Edwards, Pang, Shiu, & Chan, 2010;Piderman et al, 2015). The results of the present study are the basis upon which the ANT Foundation now plans to develop its "Spirituality" project.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decades, a shift has been made in the treatment of cancer patients from focusing on physical symptoms to seeing patients as holistic human beings with physical, psychosocial, and spiritual needs . To be diagnosed with a life‐threatening disease such as cancer can be a deeply unsettling experience that may raise existential concerns .…”
Section: Introductionmentioning
confidence: 99%